Meningkatkan Pengetahuan Anak Tentang Cara/Langkah Mencuci Tangan Yang Baik Dan Benar Pada Anak SD 018 Di Desa Pal 30 - Winessantiya; Pepi Novitasari; Ade Irma Suryani; Ummi Kalsum; Selvia Novita (Gayaku Publisher, 2022)
counseling for SD 018 children in North Bengkulu, which aims to provide socialization to SD 018 children in Pal'30 Village so they can practice good and correct hand washing. There are 3 methods carried out (1) counseling/lectures, (2) learning materials, (3) hands-on practice. Respondents were 22 children. It was found that 75% of children did not understand how to wash their hands properly according to health protocols and 25% who did not comply with health standards. After conducting counseling using these 3 methods, there was a change in knowledge and attitude in washing hands, where previously there were 25% and increased to 60%. In conclusion, according to WHO, the proper way to wash hands can be successful by using only the 3 methods, namely counseling/lectures, learning materials, and direct practice.